Primerjalna raziskava terapevtske enakovrednosti med testnim in referenčnim zdravilom fiksne kombinacije 3 miligramov benzidaminijevega klorida in 1 miligrama cetilpiridinijevega klorida pri preiskovancih z vnetim žrelom, povezanim z okužbami zgornjih dihal - Košir, Primož (Medicinski razgledi, 2015)
Cetylpyridinium chloride acts as a broad-spectrum antiseptic. Its antibacterial effect has been recognized for many years. Benzydamine hydrochloride is an indazole, a non-steroidal anti-inflammatory drug that has analgesic, anti-inflammatory, local anesthetic and antipyretic properties and has been widely used across Europe for nearly four decades. The comŽ bination of antiseptic properties of cetylpyridinium chloride and anti-inflammatory and analgesic action of benzydamine hydrochloride is therapeutically useful in the treatment of upper respiratory tract infections and inflammations.The aim of our study was to conŽ firm efficacy and safety of the combination in the treatment of sore throat associated with upper respiratory tract infections. The formulation, 3 mg benzydamine hydrochloride and 1mg cetylpyridinium chloride (Septabene lozenges, Krka, d.d.), was significantly superior to the placebo and comparable to the reference investigational medicinal product in all efficacy endpoints. There was an immediate onset of action of the tested investigational medicinal product. This was shown by the reduction in throat pain intensity and improvement in throat pain relief over the initial 15-minute interval period after drug administration. Throat pain was statistically significantly reduced for at least three hours in comparison with the placebo. Similar improvement was observed in pain relief over three hours. After four days of treatment, pain intensity was reduced for more than 85% from baseline. At the end of the treatment , the clisease was resolved in 89% of patients treated with the tested investigational medicinal product. Adverse reactions (dry mouth and heartburn) were reported in 2.54% subjects treated with the tested investigational medicinal product. The reactions were evaluated as mild and were abated within 24 hours. Both active treatments had a similar safety profile, which was clinically not significantly different from the placebo. This study demonstrated that tested investigational mediciŽ nal product is effective and well tolerated and serves as an appropriate treatment option for patients with sore throat associated with upper respiratory tract infections.
Keywords: vnetje žrela; cetilpiridinijev klorid; benzidaminijev klorid; protibolečinsko delovanje; protivnetno delovanje; antiseptično delovanje